Development and Application of an Expert Decision-Making System for Personalized Exercise Prescriptions for Children with Special Physiques. (8th August 2022) - Zhang, Li-Fang; Fang, Chun-Long; Zhou, Liang
Abstract : The expert decision-making system is developed to provide a scientific and reasonable exercise solution management platform for primary and middle school students, especially children with special physiques, such as obesity and thinness, to improve the universality and compliance of exercise prescriptions for children with special physiques. The system provides personal information management, exercise management, exercise solution formulation, data statistics, and image management functions, enables self-selection, and free combination of children exercise prescriptions, and can improve the effectiveness of such prescriptions through personalized design. The system first divides exercise prescriptions into three bigger sections: the warm-up section, the main exercise section, and the cool-down section, then subdivides them into 15 smaller sections, further chooses, matches, verifies, and revises the components of the exercise prescription according to the object's basic demographic information and body mass index and finally formulates a personalized and reasonable exercise prescription. It also can track and manage the exercise solution formulated and dynamically adjust the exercise solution according to the change of the object's body index, thus strengthening the degree of freedom and personalized characteristics of the exercise prescription.